Helicopter aeromedical service: reality and professional perspective (Research, Society and Development, 2021)
Objective: to understand the work reality and perspectives of professionals who are part of the aeromedical care team in Santa Catarina. Methodology: Exploratory, descriptive study with a qualitative focus. Seventeen interviews were conducted with professionals who are part of the helicopter aeromedical service in Santa Catarina (doctors, nurses, operational crew and aircraft pilots). Semi-structured interviews were used, transcribed, and analyzed through content analysis. Results: from the thematic content analysis, four categories emerged: attitude and knowledge as work needs; professional responsibilities and challenges; attributes for aeromedical service and expressive circumstances from the professional perspective of aeromedical care. The categories reflect issues that were present in the speeches, they show the importance of knowledge and technical aptitude for the stabilization of emergency patients in aeromedical activity. The professional challenges were represented by the unpredictability of activations, service in places with difficult access and unfavorable weather conditions. Conclusion: the study made it possible to understand the reality and perception that aeromedical service professionals have about the work they perform. As an emergency care modality, requires multiple skills of the professionals involved, demonstrating the importance of technical and cognitive capacity for the patient's clinical stabilization, anchored in knowledge of flight physiology, flight safety and navigability; combined with physical resilience. It is noticed the predominance of a hegemonic discourse, with emphasis on teamwork, communication and interprofessional trust.